IR-EcoSpectra: Exploring sustainable ex situ and in situ FTIR applications for green chemical and pharmaceutical analysis - Alina Cherniienko; Roman Lesyk; Lucjusz Zaprutko; Anna Pawełczyk (Elsevier, 2024)
In various industries, particularly in the chemical and pharmaceutical fields, Fourier transform infrared spectroscopy (FTIR) spectroscopy provides a unique capacity to detect and characterise complex chemicals while minimising environmental damage by minimal waste generation and reducing the need for extensive sample preparation or use of harmful reagents. This review showcases the versatility of ex situ and in situ FTIR applications for substance identification, analysis, and dynamic monitoring. Ex situ FTIR spectroscopy's accuracy in identifying impurities, monitoring crystallisation processes, and regulating medication release patterns improves product quality, safety, and efficacy. Furthermore, its quantification capabilities enable more effective drug development, dosage procedures, and quality control practices, all of which are consistent with green analytical principles. On the other hand, in situ FTIR spectroscopy appears to be a novel tool for the real-time investigation of molecular changes during reactions and processes, allowing for the monitoring of drug release kinetics, crystallisation dynamics, and surface contacts, as well as providing vital insights into material behaviour. The combination of ex situ FTIR precision and in situ FTIR dynamic capabilities gives a comprehensive analytical framework for developing green practices, quality control, and innovation in the chemical and pharmaceutical industries. This review presents the wide range of applications of ex situ and in situ FTIR spectroscopy in chemical, pharmaceutical and medical fields as an analytical green chemistry tool. However, further study is required to fully realise FTIR's potential and develop new applications that improve sustainability in these areas.